Potential determinants affecting the growth of China's ocean economy: An input-output structural decomposition analysis. (April 2023) - Zheng, Li; Zou, Hongyang; Duan, Xiaofeng; Lin, Zhongguo; Du, Huibin
Abstract: Developing the ocean economy has become an important strategy for economic transformation in major coastal countries. A clear understanding of what has driven ocean industrial growth is crucial for the growth of China's ocean economy to fulfill UN's Sustainable Developing Goals 14 (SDG 14). In this study, we first compiled and developed high-resolution, long-term coverage and comparable list of China's Ocean Economic Input-Output Tables (OEIOTs) for years 2007, 2012, and 2017. Subsequently, we creatively employed an SDA model to quantify ocean industrial structure linkages from an intra- and intersectoral perspective, and then examined the potential determinants of ocean industrial growth. Our results show that the intersectoral spillover effect has become the most critical driver for ocean economic development, and the average intersectoral feedback effect and spillover effect of marine industry have been stronger than those of the land industry. Notably, the continuous decline in the average intersectoral spillover has caused the loss of the total ocean economic growth. We also find that the contribution of the dynamic multiplier effect to the primary ocean industrial growth has decreased and its positive effect needs to be stimulated. The key driver of the intersectoral linkage mechanism to the secondary ocean industrial growth has expanded significantly, whereas its contribution to the tertiary ocean industrial growth has been relatively insufficient. Our findings yield clear policy recommendations for strengthen the linkage effects of different ocean industrial sectors to enhance their growth potential and upgrade the ocean economic structure for better fulfilling SDG 14.